Types and spatiotemporal change characteristics of population shrinking county seats in the Yellow River Basin - WANG Lucang, YANG Tingting (Ziyuan Kexue, 2024)
[Objective] “Shrinking county seats” is a new topic in national and regional governance. As the center of the county, a county seat is not only the center of population distribution, but also the center of comprehensive governance in the county. The shrinkage of the county seat's population has more exemplary and symbolic significance. Resolving the population shrinkage, economic decline, and slow social development problems of county seats has become an important issue in promoting urban-rural integration and achieving rural revitalization. The high-quality development of the Yellow River Basin has become a national strategy, but it is facing dual pressures of population reduction and loss. It is of great practical significance to scientifically identify the types of shrinking county seats, analyze the periodicity and stability of the shrinking process, and promote the high-quality development of the Yellow River Basin. [Method] This study used population shrinkage rate to systematically analyze the process and types of population shrinkage in county seats in the Yellow River Basin from 2000 to 2020. [Results] The study found that: (1) Population shrinkage in the county seats is mainly characterized by temporary and periodic contractions. (2) Shrinking county seats are concentrated in contiguous poverty-stricken areas, mineral resource development zones, ethnic minority settlements, and inter-provincial border areas. (3) The population in the county seats alternated between contraction and stagnation (or expansion), with the cumulative years of contraction mainly within 2 to 4 years, followed by 5 to 8 years, roughly in line with China's unique Five Year Plan periods (Kitchin Cycle) and Juglar Cycle. [Conclusion] The 381 county seats in the Yellow River Basin mainly experienced temporary and periodic contraction, which has not resulted in worrying results. But attention should be paid to the concentrated distribution areas and targeted response strategies should be formulated.